Studies in the carbohydrate field - Percival, Edmund George Vincent (The University of Edinburgh, 1938)
Evidence of Continuous Chains of α-Glucopyranose Units in starch and Glycogen

Trimethyl amylose was degraded by contact with acetyl bromide in chloroform solution to give derivatives of (a) a monosaccharide, (b) a disaccharide and (c) a trisaccharide. The disaccharide derivative was converted into a mono-acetyl hexamethyl biose by removal of the bromine residue, after which oxidation followed by methylation yielded the corresponding octamethyl methyl maltobionate (22.4%). This compound on hydrolysis with mineral acid gave rise to two cleavage fragments, crystalline tetramethyl glucopyranose (95%) and crystalline 2:3:5:6-tetramethyl γ-gluconolactone (80%). The latter was identified both by its melting point and specific rotation as well as by the physical constants of the crystalline phenylhydrazide of the corresponding acid. Hence it is concluded that only position 4 can be involved in the union of this part of the molecule with the adjoining residue, namely, tetramethyl glucopyranose in the octamethyl bionic ester, so that the 4-position is involved in the union of the contiguous glucopyranose units in amylose.

I. Evidence of Continuous Chains of α-Glucopyranose Units in Starch and Glycogen. J.Chem.Soc., 1931, 1342 • II. Evidence of the Pyranose Structure of Xylan. J.Chem.Soc., 1931, 2850. • III. The Molecular Structure of Glycogen. J.Chem.Soc., 1932, 2277. • IV. The Molecular Structure of Inulin. J.Chem.Soc., 1932, 2384. • V. The Structure of Ascorbic Acid. Chem. and Ind., 1933,52,221. • VI. Constitution of Ascorbic Acid. Nature,1.933, 131, 617. • VII. The Constitution of Ascorbic Acid. J.Chem.Soc., 1933, 1270. • VIII. Synthesis of d- and of I-ascorbic Acid and of Analogous Substances. J.Chem.Soc., 1933, 1419. • IX. Addition Compounds of the Carbohydrates, Pt.I. Potassium hydroxide- Glucose and Related Compounds. J.Chem.Soc., 1934, 1160. • X Addition Compounds of the Carbohydrates, Pt.II. Potassium Hydroxide-Sucrose. J.Chem.Soc., 1935, 648. • XI Addition Compounds of the Carbohydrates, Pt.III. Potassium! hydroxide Derivatives of Celloblase, Lactose and Galactose. J.Chem.Soc., 1936, 1765. • XII. Monomethyl Hexoses, Pt. I. Constitution of the Supposed 4-Methyl Glucose. J.Chem.Soc.,1935, 873. • XIII. Monomethyl Hexoses, Pt. II. A Revision of the Constitutions of the Supposed 4-Methyl Galactose and 4-Methyl Mannose of Paceu, and their Formulation as 6-Methyl Galactose and 2-Methyl Mannose Respectively J.Chem.Soc.,1935, 640. • XIV. The Methylation of Glucosephenyl osazone and its Formulation as a Derivative of Fructopyranose. J.Chem.Soc., 1935, 1398. • XV. The Structure of Osazones and the Isolation of a New hexosazone Anhydride. J.Chem.Soc., 1936, 1770. • XVI. Sugar Osazones and Their Anhydrides. J.Chem.Soc., 1937, 1320. • XVII. Acetylation of Agar. Nature, 1936, 137, 997. • XVIII. Structure of Agar-Agar Nature, 1937, 139, 512. • XIX. The Acetylation of Agar-Agar and the Isolation of 2:4:6-Tri-methyl α-d-Galactose by Hydrolysis. J.Chem.Soc., 1937, 1615. • XX. Investigations on the Configuration of Carbohydrates by Conductivity Measurements in Boric Acid Solution. J.Chem.Soc., 1937, 1920.